A vision from the future beyond 3G TDD. - Ping Zhang (IEEE Communications magazine)
This article introduces the visions and developments of Beyond 3G mobile communications in the China TDD Special Work Group. System structure, radio transmission design, radio resource management, and demonstration system implementation are covered. In system structure, the concept of group cell and the architecture of distributed antennas are introduced. The radio link transmission design presented in this article includes the radio frame structure, multiple access scheme, and promising key techniques. Link-level simulations prove the advantages of the design. The radio resource management strategies are introduced to optimize the system performance. The B3G TDD demonstration system being built by the TDD Special Work Group is also shown finally.